In good faith : Arabic translation and translators in early modern Spain - Gilbert, Claire M. (University of Pennsylvania Press, 2020)
Claire M. Gilbert develops the notion of ""fiduciary translation"" and uses it to illuminate the ways in which Arabic-Spanish translators in early modern Spain made themselves indispensable for the administration of the empire, despite the increased animosity Arabic speakers faced in the age of the Inquisition